Computation of hypersonic re-entry flows - Tan, Samuel Peng Yu (2014)
This paper presents a computational study of the ELECTRE experiments in the HEG facility. A theoretical study of all the 9 shots conuducted in the experiment will be carried out to compare the theoretical heat flux distributions with the experimental values. ANSYS Fluent will then be used to simulate the flow the Electre model, which is a spherically capped blunted cone. The results are then compared with both the experimental and theoretical values.